The Economics of Leisure and Tourism / Environments, Markets and Impacts - Tribe, John (Butterworth Heinemann, 1995)
This book tackles issues that will affect the sector into the next century including globalization, virtual leisure, and the grey and green revolutions. Preface, Acknowledgements, Organizations and Markets in Leisure and Tourism, Leisure and Tourism Organizations and the External Environment, Investing in Leisure and Tourism, Leisure and Tourism Impacts on the National Economy, International Aspects of Leisure and Tourism, Leisure and Tourism and Environmental Issues, Integrated Case Studies, Index.